Designing Promotional Media and Art Activities to Promote Cultural Learning in Lamphaya Community, Nakhon Pathom Province - Charoensuk, Patiphan; Asavalertplakorn, Chutipa; Wannawong, Manassanan; Chutataweesawas, Sirikoy (DEC Journal : Art and Design, 2025)
Lumphaya is a historically significant trading community that has declined in recent years. Many younger community members are unaware of its cultural background, highlighting the need to promote cultural preservation. This research aimed to: 1) explore the identity of the Lumphaya community; 2) design art-based activities to communicate cultural knowledge to both locals and tourists; and 3) study the outcomes of these activities. The research involved purposive sampling (the abbot and museum staff) for interviews, and accidental sampling for surveys and activity participation. A total of 77 participants were included: 43 respondents to the activity design questionnaire and 32 activity participants. The research tools consisted of: 1) interview guidelines for activity design; 2) a questionnaire on activity design; and 3) a satisfaction evaluation form. Qualitative data were analyzed descriptively, while quantitative data were analyzed using descriptive statistics (mean scores). Findings revealed 1. Two key aspects of community identity: 1) Historical significance, represented by the community museum that houses artifacts reflecting local ways of life; 2) Cultural identity as a riverside community with Chinese and Mon ethnic groups engaged in agriculture and trade. 2. Four suitable formats of promotional media and activities were developed: 1) Promotional and directional signage 2) Informational signs for key artifacts and map 3) Lumphaya Story booklet 4) Stamp Stories postcard printmaking kit. 3. Overall satisfaction was rated as good, with the highest mean score for the informational signage ( = 4.41). For further development, the media and activities can be adapted as educational tools in schools to promote cultural appreciation and can also be applied in other communities.